2001
DOI: 10.1128/iai.69.7.4430-4437.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of a Neuraminidase Gene fromArcanobacterium pyogenes

Abstract: Arcanobacterium pyogenes is an opportunistic pathogen, associated with suppurative infections in domestic animals. In addition to pyolysin, a pore-forming, cholesterol-binding toxin, A. pyogenes expresses a number of putative virulence factors, including several proteases and neuraminidase activity. A 3,009-bp gene, nanH, was cloned and sequenced and conferred neuraminidase activity on an Escherichia coli host strain. The predicted 107-kDa NanH protein displayed similarity to a number of bacterial neuraminidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 55 publications
1
40
0
1
Order By: Relevance
“…In addition, two neuraminidases, H (nanH: 40%) and P (nanP: 38%) were found in this study. Previous studies (Jost et al, 2001) showed that all investigated T. pyogenes isolates recovered from different types of infection were positive for nanH activity, and 64.2% of these isolates harboured the nanP gene. Both the nanH and nanP genes also occurred in all isolates recovered from the uterus of dairy cows (Silva and Lobato, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, two neuraminidases, H (nanH: 40%) and P (nanP: 38%) were found in this study. Previous studies (Jost et al, 2001) showed that all investigated T. pyogenes isolates recovered from different types of infection were positive for nanH activity, and 64.2% of these isolates harboured the nanP gene. Both the nanH and nanP genes also occurred in all isolates recovered from the uterus of dairy cows (Silva and Lobato, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…An A. pyogenes BBR1 nanH insertion deletion mutant exhibited neuraminidase activity (16), suggesting that a second neuraminidase gene was present in this strain. Plaques from a GEM-12 library of A. pyogenes BBR1 genomic DNA (16) were overlaid with MUAN-containing top agar and were visualized under UV light.…”
Section: Resultsmentioning
confidence: 92%
“…A. pyogenes strain BBR1 was isolated from a bovine abscess. A. pyogenes strain NANH-1, in which the entire nanH gene was deleted and replaced with an erythromycin resistance cassette, was described previously (16). Other A. pyogenes strains used in this study were obtained from veterinary diagnostic laboratories or personal collections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations